Three-Port Full-Bridge Bidirectional Converter for Hybrid Dc/Dc/Ac Systems - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2020)
Sustainable solutions such as renewable energies, distributed generation, energy storage, and electric vehicles require power conversion and advance control techniques. This process is usually done in two stages by more than one power converter, specially in hybrid systems, increasing power losses and costs. The configuration with two dc stages and one ac port is widely used in several applications, such as grid-connected photovoltaic inverters; fuel cells, hybrid and electric vehicles; and ac/dc microgrids. Thus, three-port topologies have been developed to operate such systems, most of them comprising multiple power processing stages for the connection of the different elements. This article proposes a three-port full-bridge converter with a single power processing stage for dc/dc/ac systems. The ac port can be single-phase or three-phase, using two legs like an H-bridge or three legs like the conventional three-phase inverter. In both configurations, each leg is used as an inverter and as a buck-boost converter at the same time. The converter is able to manage the power flow among three ports with just four or six switches through a multivariable control strategy. Simulation and experimental results show the capability of the converter to manage the interaction between a battery and a capacitor connected to the grid achieving a fast dynamic response, bidirectional capability in all ports and reduction of components. © 1986-2012 IEEE.